FOXP3, IL2R, CD8A and RORγ gene expression in peripheral blood leukocytes of healthy people and patients with arterial hypertension - L. V. Topchieva; V. A. Korneva; I. E. Malysheva (Медицинская иммунология, 2022)
Impaired balance of T regulatory and T effector lymphocytes has recently been considered as an important pathogenetic link in arterial hypertension (AH). There are, however, contradictory literature data about contents of these cells in the patients with hypertension, or obtained in experimental animal models of induced hypertension. Most results about changed patterns of immune cells in cardiovascular diseases were obtained by means of flow cytometry. There are also some works on expression of genes encoding surface and cytoplasmic differentiation antigens of immune cells in the patients with cardiovascular pathologies. These results coincide with the data obtained with flow cytometric techniques. Purpose of the present study was to analyze of the levels of gene transcripts encoding differentiation markers of regulatory (FOXP3, IL2R) T cells, effector T subpopulations (T helpers 17 (RORγ), and CD8 lymphocytes (CD8A) in healthy subjects and the patients with arterial hypertension (stages I-II). We examined healthy individuals (40 people, 20 men and 20 women), 27 patients with hypertension who did not receive antihypertensive therapy (14 men and 13 women), 26 hypertensive patients taking β-adrenergic receptor blockers (metoprolol or bisoprolol), including 12 men and 14 women. The relative levels of transcripts in peripheral blood leukocytes were assessed by real-time RT-PCR. It was shown that the transcriptional activity of FOXP3, IL2R, RORγ, and CD8A genes in peripheral blood leukocytes of the diseased people was significantly higher than in healthy individuals (p < 0.01). This finding may indicate an increased number of circulating T regulatory lymphocytes, CD8+ cells and T helpers 17 in hypertensive patients, and activation of T cell immunity in these patients. There were no statistically significant gender differences in FOXP3, IL2R, RORγ and CD8A gene expression in leukocytes, both in the group of healthy people and in hypertensive patients. The patients receiving cardioselective β-adrenergic receptor blockers (metoprolol and bisoprolol) exhibited lower expression of these genes, thus, probably, indicating antiinflammatory and immunomodulatory properties of these drugs.